2015
DOI: 10.1002/tcr.201500231
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Carbons: Looking Beyond Their Perception as Adsorbents, Catalyst Supports and Supercapacitors

Abstract: The discovery of carbon nanoforms, and especially graphene, has opened up new directions of science and technology. Many applications are based on the unique properties of graphene, such as its high electrical and thermal conductivity, strength, flexibility, photoactivity and transparency. Inspired by the emerging graphene science, we directed our efforts to the exploration of new applications of nanoporous (microporous) carbons. Their matrix is built of distorted graphene layers, between which pores with size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…This applies to various types of materials such as nanoporous hard carbon microspheres [70], fiber-based nanoporous carbon [71], nanoporous carbon tubes [72], nanoporous carbon films [73] or activated carbon [74]. The graphitic nature, given by sp 2 hybridization, provides the large surface area in the interior of the foam scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to various types of materials such as nanoporous hard carbon microspheres [70], fiber-based nanoporous carbon [71], nanoporous carbon tubes [72], nanoporous carbon films [73] or activated carbon [74]. The graphitic nature, given by sp 2 hybridization, provides the large surface area in the interior of the foam scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…This set of patents mentions the bases of the chemical activation process (carbonization of lignocellulosic materials with metallic chlorides) and of the thermal or physical activation (slight gasification of chars with water vapor or carbon dioxide at elevated temperatures) and also the specific equipment for thereof. The factory for full-scale activated carbon production was built by that time in Ratibor, now named Raciborz (Poland), and still operates, being so the world's oldest industrial activated carbon manufacturing plant [10,11].…”
Section: Historic Perspectivementioning
confidence: 99%
“…In addition, the charge storage mechanism of the graphene paper electrode in the K 3 Fe(CN) 6 ‐Na 2 SO 4 electrolyte is diffusion‐controlled. It is reported that carbon‐based materials often show electrical double layer capacitance . The reaction mechanism of the graphene paper electrode was changed from a surface controlled to a diffusion‐controlled reaction with the present of redox electrolyte.…”
Section: Redox Ions In Electrolytementioning
confidence: 99%